Toll-like receptor 4 in pancreatic damage and immune infiltration in acute pancreatitis - Mattke, Jordan; Darden, Carly M.; Lawrence, Michael C.; Kuncha, Jayachandra; Shah, Yumna Ali; Kane, Robert R.; Naziruddin, Bashoo (Frontiers in Immunology, 2024)
Acute pancreatitis is a complex inflammatory disease resulting in extreme pain and can result in significant morbidity and mortality. It can be caused by several factors ranging from genetics, alcohol use, gall stones, and ductal obstruction caused by calcification or neutrophil extracellular traps. Acute pancreatitis is also characterized by immune cell infiltration of neutrophils and M1 macrophages. Toll-like receptor 4 (TLR4) is a pattern recognition receptor that has been noted to respond to endogenous ligands such as high mobility group box 1 (HMGB1) protein and or exogenous ligands such as lipopolysaccharide both of which can be present during the progression of acute pancreatitis. This receptor can be found on a variety of cell types from endothelial cells to resident and infiltrating immune cells leading to production of pro-inflammatory cytokines as well as immune cell activation and maturation resulting in the furthering of pancreatic damage during acute pancreatitis. In this review we will address the various mechanisms mediated by TLR4 in the advancement of acute pancreatitis and how targeting this receptor could lead to improved outcomes for patients suffering from this condition.